Penguatan Fungsi Pengawasan Legislatif terhadap Eksekutif Pasca Putusan Mahkamah Konstitusi - Rachman, Irfan Nur (Mahkamah Konstitusi Republik Indonesia, 2011)
The Constitutional Court in its decision Number 23-26/PUU- VIII/2010 have been cancelled the applicability of article 184, paragraph (4), which regulates the amount of quorum and approval of quorum in the decision-making process in the Forum related to the plenary meeting house “our opinion the proposal on the right.” In its legal considerations, the Constitutional Court confirmed that the provisions of quorum and the number of quorum approval of 3 / 4 shall be replaced with provisions in decision making on the basis of “simple majority”. This has an impact on the strengthening of the system of checks and balances for the role of legislative control the Executive branch that the abuse of power by the Executive branch can prevent.